ISLAMIC CONCEPT OF WAQF: CHALLENGES AND PROSPECTS WITH REFERENCE TO THE JAMMU AND KASHMIR MUSLIM WAQF BOARD - Zahid Ahmad Dar (Airlangga International Journal of Islamic Economics and Finance, 2020)
Allah sent Adam (A.S.) and His Kin on earth and made them to pass through diverse phases of life following His guidance from time to time through various prophets for each community, nation. In a society, He made them to depend on one another by bestowing some over the other to maintain the integrity of brotherhood, cooperation and so on. The challenging aspect in this way is the financial security which works against the greedy nature of a Man. In addition to Huqūq al-Allah, Islam also stresses on Huqūq al-‘Ibād, wherein helping someone economically becomes an important facet. To bring this idea into action, an institution has been developed named as ‘Waqf’ which provides all possible help to the downtrodden and marginalized section of the society. It plays very substantial role in the overall prosperity of both Muslims and non-Muslims. This paper aims at deliberating on present scenario of Waqf in the Union Territory of Jammu and Kashmir, India and highlights challenges to this institution, a barrier in overall development and security of a well-to-do society.